"Mismatch" in the Search for "Effortless Permanence": Discussion of "Rethinking Therapeutic Action". Issue 3 (1st September 2020) - Leddick, Katherine H.
Abstract : In this discussion of Kenneth Frank's paper "Rethinking Therapeutic Action: Finding Commonality in Diversity, " critical elements of research on memory reconsolidation are specified for transformational change through psychotherapy and psychoanalysis. Central functions of the therapeutic relationship are put forth, including the use of the relationship for delineating often dissociated "maladaptive emotion schemas" and developing tolerance for necessary experiences of activated relational trauma. The therapeutic relationship is central in the process of tolerating destabilized traumatic memory and making it available for update. Often the therapeutic relationship offers an experience of "mismatch" or new experience with links to the emotional schema, facilitating a key component of change.